Gambaran Stres Kerja Petugas Rekam Medis di Rumah Sakit Kota Surabaya - Syafira Nulia; Ian Rahmadhani; Aryo Kuncoro; Azundha Rahmadani; Salshabilla Fitri; Lilis Masyfufah A. S; Diah Wijayanti S (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
Work stress is a state of physical and psychological imbalance that can interfere with the implementation of tasks in achieving work performance. The purpose of this study was to determine the description of the work stress of medical record officers, for that a survey was conducted and questionnaires were distributed to obtain data. The population in this study were medical record officers with a sample size of 40 people, using the non-probability sampling technique with the quota sampling method. The three variables studied were the work environment, technological developments and work motivation. The number of questionnaires used in this study were 40 questionnaires. Then quantitative data analysis was carried out categorizing the scores on a high, medium and low scale with the help of the SPSS version 25 application program. According to statistical calculations, the results of the assessment of work environment variables were 52.5% in the high category. While the variable of technological development is 57.5% in the high category and work motivation is 72.5% in the medium category.